2001
DOI: 10.1146/annurev.genet.35.102401.090756
|View full text |Cite
|
Sign up to set email alerts
|

Translational Regulation and RNA Localization in Drosophila Oocytes and Embryos

Abstract: Translational control is a prevalent means of gene regulation during Drosophila oogenesis and embryogenesis. Multiple maternal mRNAs are localized within the oocyte, and this localization is often coupled to their translational regulation. Subsequently, translational control allows maternally deposited mRNAs to direct the early stages of embryonic development. In this review we outline some general mechanisms of translational regulation and mRNA localization that have been uncovered in various model systems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
214
0
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(227 citation statements)
references
References 256 publications
4
214
0
9
Order By: Relevance
“…These patterns range from nuclear accumulation during the early cleavage stages to the enrichment at the boundary between adjacent myotubes. Studies of mRNA localization patterns of protein-coding genes in yeast (e.g., ASH1) (Long et al 1997) and flies (e.g., bicoid, oskar, gurken) (for review, see Johnstone and Lasko 2001) have shown that the subcellular localization of specific RNAs is essential for normal development. Thus, enrichment of lncRNAs in specific subcellular compartments may be of fundamental importance for the regulatory functions of ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns range from nuclear accumulation during the early cleavage stages to the enrichment at the boundary between adjacent myotubes. Studies of mRNA localization patterns of protein-coding genes in yeast (e.g., ASH1) (Long et al 1997) and flies (e.g., bicoid, oskar, gurken) (for review, see Johnstone and Lasko 2001) have shown that the subcellular localization of specific RNAs is essential for normal development. Thus, enrichment of lncRNAs in specific subcellular compartments may be of fundamental importance for the regulatory functions of ncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several other proteins acting as translational regulators have been reported in the fly embryo and oocyte [50][51][52][53][54][55][56][57], and in other eukaryotic species [58][59][60], oftentimes in a developmental context. These findings hint at the possibility that the regulatory principle implemented by bicoid protein and caudal mRNA in Drosophila may be at work also in other developmental systems.…”
Section: Discussionmentioning
confidence: 99%
“…Since these regulatory proteins bind to DNA, it is plausible that they could also bind to mRNA, thereby regulating translation; this is known to happen in the large class of homeodomain proteins [45][46][47] and for the Argonaute family proteins [48,49], for several other proteins that fulfill important functions in the Drosophila embryo and oocyte [50][51][52][53][54][55][56][57], but also in other eukaryotic species [58][59][60] and in prokaryotes [61][62][63][64][65][66][67]. Intuitively, each mRNA molecule could act as an independent sensor of the input concentration, and averaging over these multiple sensors could reduce the input noise and thereby allow for more effective information transmission at low input concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Translational control and mRNA localization, achieved via a variety of mechanisms, are important for the delivery of certain cytoplasmically synthesized proteins to their functional destinations within cells of animals (Johnstone and Lasko, 2001;Palacios and Johnston, 2001), plants (Choi et al, 2000), and yeast (Zoladek et al, 1995;Lithgow et al, 1997;Corral-Debrinski et al, 2000). In general, these strategies seem to reinforce targeting information present within the protein products themselves.…”
Section: Introductionmentioning
confidence: 99%